Two main factors in the formation of the wing venation of Diptera. - Ussatchov, D. A. (Contributions to Entomology = Beiträge zur Entomologie, 1970)
If we examine various types of the venation of the wings of Diptera, we find and distinguish two basic processes which determine the formation and the development of the system of veins and cells, the process of costalization and the process of stabilization. As a more general and instructive arrangement of the mechanisms under consideration, a series of five infa-orders was established, and an attempt was made to explain the progressive changes in this series by the assumption that the existing processes represent the interacting sides of a contradiction. As a result of the habitat conditions, one of these sices becomes the main trend.